Modelling the effect of grooved barrels on the performance of single screw extruders - Gaspar-Cunha, A. (2018)
Single screw extruders containing grooved barrels are used in many industrial extrusion lines, for example to manufacture plastics pipes and blown film. Through an increase of the drag friction forces between the polymer and the barrel, the conveying capacity of the screw is enhanced, yielding higher outputs and better process stability. This chapter presents and assesses computationally models for considering the effect of the presence of longitudinal or helical grooves near to the inlet port of the barrel of single screw extruders. The results obtained demonstrate that the existence of grooves clearly improves the performance of the extruder.